Strenghtening of the Biomedical Engineering Career Identity in Mexico - Ayala-Perdomo, R. (Revista Mexicana de Ingenieria Biomedica, 2019)
With the purpose of betterment of the Biomedical Engineering (BME) profession in Mexico, four cases are presented of identified opportunity areas situations that could strength the activity frame of such profession, along with con-crete proposals of actions that can provide with solutions. Strengthening the identity of BME professionals in Mexi-co, giving a sense of pertinence and establishing a solid and compromised community, better work opportunities could be achieved in the Country.